2021
DOI: 10.1002/mbo3.1158
|View full text |Cite
|
Sign up to set email alerts
|

Spatially explicit depiction of a floral epiphytic bacterial community reveals role for environmental filtering within petals

Abstract: The microbiome of flowers (anthosphere) is an understudied compartment of the plant microbiome. Within the flower, petals represent a heterogeneous environment for microbes in terms of resources and environmental stress. Yet, little is known of drivers of structure and function of the epiphytic microbial community at the within‐petal scale. We characterized the petal microbiome in two co‐flowering plants that differ in the pattern of ultraviolet (UV) absorption along their petals. Bacterial communities were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 81 publications
(149 reference statements)
0
15
0
Order By: Relevance
“… 2012 ; Hayes et al . 2021 ), whereas a one-square-meter plot may be a rather homogeneous niche for plants. Likewise, a soil particle is characterized by a strong gradient of abiotic variables and thus provides various niches (Sexstone et al .…”
Section: Introductionmentioning
confidence: 99%
“… 2012 ; Hayes et al . 2021 ), whereas a one-square-meter plot may be a rather homogeneous niche for plants. Likewise, a soil particle is characterized by a strong gradient of abiotic variables and thus provides various niches (Sexstone et al .…”
Section: Introductionmentioning
confidence: 99%
“…Sampling a single leaf or petal means integrating over multiple microbial niches characterized by different availabilities of water, nutrients, and plant metabolites (Karamanoli et al, 2012, Hayes et al, 2021, whereas a one-square-meter-plot may be a rather homogenous niche for plants. Likewise, a soil particle is characterized by a strong gradient of abiotic variables and thus provides various niches (Sexstone et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…Microbial dispersal via bees, the most important pollinators of cultivated strawberry (Klatt et al, 2014), can be potentially extensive and thus increase α-diversity (e.g., in bacterial communities), but high rates of microbial dispersal can also homogenize microbial communities, thereby contributing little to community differentiation (along cPCoA1) relative to other functional groups (Figure 4c,d). We found that bacterial taxa associated with bee visitation (post-hoc tests, Appendix S1; Table S7) often belong to Acinetobacter (including A. nectaris), Methylobacterium, Rosenbergiella and Sphingomonas, which are common in nectar (Pozo et al, 2014) and flowers (Hayes et al, 2021;Wei & Ashman, 2018). Relative to bees, the effect of visitation by true bugs and flies on microbial community differentiation may reflect microbial dispersal limitation mediated by these abundant functional groups.…”
Section: Discussionmentioning
confidence: 93%
“…whereas other microbes (Table S7) may be opportunistic or proliferate on flowers via mechanisms yet to be explored. Overall, the direct and indirect effects of flower abundance underlined the importance of considering this driver in the principles of microbiome assembly in flowers, in addition to other floral traits (e.g., volatiles, ultraviolet patterns; Hayes et al, 2021;Schaeffer et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation